PERAN APARATUR PEMERINTAH DESA DALAM PEMBINAAN PEMUDA DI DESA BRAJA ASRI SEBAGAI UPAYA PEMBENTUKAN KEADABAN KEWARGANEGARAAN (CIVIC VIRTUE) - Dewi, Yulianti Puspita; Pitoewas, Berchah; Adha, Muhammad Mona (STKIP Persada Khatulistiwa Sintang, 2022)
The village government as a stakeholder who is responsible for developing the potential that exists in the village, one of which is the potential of human resources. Youth is an important component in the village as a partner of the village government to work together to advance the welfare of the village. Based on the Republican Theory of Citizenship that individual freedom exists in a guarantee of state security that is under the legal order and the virtues of citizens (civic virtues) to be able to participate in it. The purpose of this study is to analyze and describe the role of the village government in carrying out youth development efforts in Braja Asri Village as an effort to establish civic virtue. The research method used is a descriptive method with a qualitative approach. Data collection techniques are carried out by means of observation, documentation, and interviews. Based on the results of the study, it shows that the implementation of guidance from the Braja Asri Village government has not been effective because the village government is still focusing on the physical development of the village, the lack of motivation from the youth themselves, the personal busyness of each young man. This affects the process of forming civic virtue in the youth because there needs to be good cooperation between fellow components, namely the village government and the youth.Keywords: Village Government, Youth Development, Citizenship Civilization